PELATIHAN TATA KELOLA MANAJEMEN LEMBAGA KEUANGAN MIKRO AGRIBISNIS (LKMA) KABUPATEN KENDAL - Purwanto, Edy; Purwanto, Dedik; Aidin, Muhammad (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Kendal Regency is one of the regencies in Central Java Province with economic characteristics that are dominated by the agricultural sector. The inability of farmers to access formal sources of capital is due to the lack of easy credit application procedures and the absence of required collateral. The Minister of Agriculture has implemented the PUAP program since 2008 by growing and developing Agribusiness Microfinance Institutions (LKMA) through villages receiving BLM-PUAP funds. The number of Kendal Regency LKMAs during 2008-2015 reached 277 Gapoktan spread across 20 sub-districts. In 2022, there will be 249 LKMAs that will no longer be active and the remaining 28 LKMAs will still be active and 15 of them will have legal entities. The method of implementing the activities carried out in this service is in the form of counseling and training. The results of this community service are 1) LKMA management understands and knows the form of business that will be used to process business permits and will prepare business management governance guidelines according to mutual agreement; 2). LKMA management is able to make a SWOT analysis and know the strategies that will be implemented; and 3). LKMA management is motivated to improve and develop businesses for the progress and welfare of farmers.